The Public Procurement Administrative Court in the Period 2012-2014 - Becerra Farfán, María Hilda (2015)
This article shows the results of the Public Procurement Administrative Court’s performance from 2012 to 2014, mainly referred to opportunity and predictability on resolutions issuing process, supporting on statistics the evolution of the caseload as well as the time record of closing the procedures related to matters of Administrative Court’s jurisdiction which had a direct effect on the public procurement contracts’ efficiency.Additionally, we go through some Plenary Chamber Rulings, witch jointly with uniform interpretation criteria are the best mechanism to ensure equality in law application and thus institutional framework of Public Procurement Administrative Court.